DEVELOPMENT OF GROUP DYNAMICS FOR MEMBER'S BUSINESS SUCCESS (PPM activities at the “Pinter” Women Farmers Group in Cibiru Wetan Village Cileunyi District, Bandung Regency, West Java) - Unang Yunasaf; Marina Sulistyati; Syahirul Alim (Fakultas Peternakan, Universitas Padjadjaran, 2022)
The existence of groups, including the Women's Farmers' Group, is an important part of improving the quality of its members. This study aims to examine: (1) how the conditions of the Cibiru Wetan “Pintar” Women Farmer Group, Cileunyi District, Bandung Regency, West Java Province are seen from the implementation of their functions as a farmer group, and (2) how the implementation of PPM in “Pintar” KWT in maintaining dynamics in his group. The service activities carried out are aimed at helping Cibiru Wetan “Pintar” KWT in maintaining the dynamics of the group as part of the Hybrid integrative PPM for the January-February 2022 period. The main activities carried out are mentoring the implementation of smart expo activities, and Focus Group Discussion (FGD) developing group dynamics . The results of the study show that KWT seen from the function of the group has carried out its function, especially as a learning class, and a vehicle for collaboration. The PPM activities carried out at the “Pintar” KWT have helped the implementation of the Smart Expo activities well. The results of the FGD as an effort to develop group dynamics show that KWT “Pintar” is classified as having good group dynamics.Keywords: Group dynamics, farmer women, business success